LEVEL OF PATIENT SATISFACTION TOWARDS PHARMACY SERVICES IN KIMIA FARMA TALANGSARI PHARMACY - Rina Dias Agustina; Amaliyah Nurul Hidayah (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2021)
Pharmacy is one of the health service place that has product and service activities that are highly dependent on patient satisfaction. Patient satisfaction can be used as a benchmark for companies to develop their business in the future. The purpose of this study was to determine the level of patient satisfaction with pharmaceutical services at Kimia Farma Pharmacy Talangsari Jember. The type of this research was qualitative descriptive using cross sectional study. The population were patients who came to buy prescription or non-prescription drugs at the Kimia Farma Pharmacy Talangsari Jember in June 2020 with a total samples of 100 patients. The result showed that patient satisfaction to the services at Kimia Farma Pharmacy Talangsari Jember were quiet satisfied in reliability dimensions (60%) and tangible dimensions (55%) also in responsiveness dimensions (48%) and less satisfied in empathy dimensions (54%) and assurance dimensions (41%). It can be concluded that the level of patient satisfaction with pharmaceutical services at Kimia Farma Pharmacy Talangsari Jember were  Keywords: level of satisfaction, quality of service